IMPROVING PATRONAGE SERVICES FOR EXPECTANT MOTHERS AND CHILDREN, PRIMARY PREVENTION OF CONGENITAL ANOMALIES - Kasimova D. A. (American Journals Publishing, 2024)
The prevalence of congenital anomalies among children, the study of risk factors and the development of a scientifically based system of measures to improve the patronage of future mothers and children to eliminate them.